2012
DOI: 10.1017/s0022215112002058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of peritonsillar infiltration of tramadol and lidocaine for the relief of post-tonsillectomy pain

Abstract: Peritonsillar infiltration of tramadol provided pain control in the first 6 hours post-tonsillectomy which was comparable to that of lidocaine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Seven of them were considered inappropriate for inclusion in the final analysis due to methodological constraints or non‐English full‐text publication. The selected articles consisted of 12 RCTs enrolling a total of 972 children, among which 345 were assigned to the tramadol peritonsillar infiltration group and the remaining 627 in the placebo or active comparator groups. All of these studies met the criteria to be included in the final qualitative appraisal, whilst 8 RCTs incorporating both a comparison to the placebo group and tramadol dosing of 2 mg/kg were deemed eligible to be included in the quantitative analysis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven of them were considered inappropriate for inclusion in the final analysis due to methodological constraints or non‐English full‐text publication. The selected articles consisted of 12 RCTs enrolling a total of 972 children, among which 345 were assigned to the tramadol peritonsillar infiltration group and the remaining 627 in the placebo or active comparator groups. All of these studies met the criteria to be included in the final qualitative appraisal, whilst 8 RCTs incorporating both a comparison to the placebo group and tramadol dosing of 2 mg/kg were deemed eligible to be included in the quantitative analysis .…”
Section: Resultsmentioning
confidence: 99%
“…The selected articles consisted of 12 RCTs enrolling a total of 972 children, among which 345 were assigned to the tramadol peritonsillar infiltration group and the remaining 627 in the placebo or active comparator groups. All of these studies met the criteria to be included in the final qualitative appraisal, whilst 8 RCTs incorporating both a comparison to the placebo group and tramadol dosing of 2 mg/kg were deemed eligible to be included in the quantitative analysis . Those implementing a common tool for pain intensity evaluation, namely the CHEOPS, or providing data regarding the time interval to first analgesic demand were finally included in the quantitative analysis of postoperative pain control .…”
Section: Resultsmentioning
confidence: 99%
“…Our option for using tramadol in this study is based on the fact it has been proven safe, with irrelevant side effects in children [17], although it still needs good scientific evidence [18]. Previous experimental [10,11,19] and clinical studies [6,20], comparing tramadol infiltration with local anesthetics, showed that this procedure resulted in local anesthesia for minor surgeries in adults [6,7] and children [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol has been demonstrated to have local analgesic effect in previous studies in adults [4,5] and children [6][7][8][9]. Besides being a weak synthetic opioid, tramadol inhibits the reuptake of monoaminergic neurotransmitters (5-hydroxytryptamine and noradrenaline) and has a local anestheticlike action on peripheral nerves [10] similar to lidocaine 1% [11].…”
Section: Introductionmentioning
confidence: 99%
“…2 Cost-utility analysis and Quality-Adjusted Life Years calculation are already in use in a variety of ENT settings. The VAS method has many advantages, due to its simplicity, and is widely used in otolaryngological research; examples include RCT assessment of tonsillectomy pain control, 45 comparison of topical anaesthetic agents for transoral rigid laryngoscopy, 46 and validation of self-assessment of smell impairment. 38 When comparing treatments for early laryngeal cancer, laser excision is suggested to have a slightly higher cost utility due to the decreased cost of salvage.…”
Section: Select Methodsmentioning
confidence: 99%